The Ginsenoside Exhibits Antiosteoporosis Effects in Ketogenic-Diet-Induced Osteoporosis via Rebalancing Bone Turnover - Liu, Qi; Zhou, Jian; Yang, Zhou; Xie, Chuhai; Huang, Yan; Ling, Long; Cao, Yanming; Hu, Hailan; Hua, Yue (Frontiers in Pharmacology, 2021)
Purpose: The ginsenoside is wildly used in the China for therapeutic and healthcare applications. Ginsenoside-Rb2 has shown the anti-osteoporosis effects in ovariectomized rats. However, the protective eﬀects on osteoporosis induced by ketogenic diet(KD) is unknown. Therefore, this study was aimed to evaluate the effects of ginsenoside-Rb2 on KD-induced osteoporosis. Methods: Thirty mice were randomly divided into three groups: the sham, KD, and KD+Rb2 groups. The bone micro-structures, the biomechanical properties, the concentrations of serum bone alkaline phosphatase (BALP) and tartrate-resistant acid phosphatase (TRACP), as well as the protein expression of osteocalcin (OCN), peroxisome proliferation-activated receptor γ (PPAR-γ) and TRACP, were evaluated after 12 weeks intervention. Results: The results showed that the KD significantly induced bone loss and impaired biomechanics. Ginsenoside-Rb2 significant attenuate bone loss and maintained biomechanics in the cancellous bone. The bone volume fraction was increased from 2.3 to 6.0% in the KD+Rb2 group than that in KD group. Meanwhile, the ginsenoside-Rb2 maintained the biomechanical strengths in the cancellous bone. Ginsenoside-Rb2 eﬀectively increased serum BALP and decreased TRACP, and up-regulated OCN and down-regulated TRAP, PPAR-γ and cathepsin K in KD mice. Conclusions: This study demonstrated that ginsenoside-Rb2 retarded bone loss and maintained the biomechanics under KD. The underlying mechanism might that the ginsenoside-Rb2 inhibited bone resorption process and induced osteogenic differentiation, which providing evidence for ginsenoside as an alternative option for osteoporosis induced by KD.